AB0966 In vitro effects of cuivramine and glucosamine sulfate on the IL-1β stimulated C-20/A4 chondrocyte cell line, a comparative study. (23rd January 2014) - Rousset, F.; Lardy, B.; Grange, L.; Gaudin, P.; Morel, F.
Abstract : Background: The pathogenesis of primary osteoarthritis involves an imbalance between anabolic and catabolic pathways in chondrocytes where the reactive oxygen species (ROS) could play a central role. The expression of matrix metalloproteinases (MMPs), chondrocyte hypertrophy and apoptosis are the main features of the pathology. NADPH oxidase Nox4 is one of the 7 ROS generating Nox members expressed in human. It was shown to be expressed in human primary chondrocytes. Nox4 displays a constitutive NADPH oxidase activity that was previously reported to modulate proMMP1 expression and apoptosis of the C-20/A4 cell line. This pathway is down regulated by heme oxygenase-1 (HO-1). Glucosamine sulfate (GS), a basic structural element that composes cartilage proteoglycans is also a dietary supplement approved as a symptomatic slow-acting drug for osteoarthritis (SYSADOA). However, impact of GS on structural features of OA is relatively modest. To go further, Cuivramine (CA), a new dietary supplement containing GS (78.9%), copper sulfate (0.105%) and ginger root extract (5.26%) has been developed. Objectives: To compare in vitro the effects of CA and GS on IL-1β stimulated C-20/A4 chondrocytes. Impact on ROS production (1), related MMPs expression (2), chondrocyte apoptosis (3) and mechanisms of action (4) has been investigated. Methods: The antioxidant effects of GS and CA were investigated on HEK 293 TRex cells, a reproducible and reliable cell model to study Nox4. MMP expression and apoptosis were assessed on the human C-20/A4 chondrocyte cell line. The cells were pre-treated with 100 or 500μg/ml CA or GS during 96h. Then, they were stimulated by 2ng/ml IL-1β for 24h to assess the secretion of ADAMTS5, proMMP1 and proMMP13 or 96h to evaluate caspase 3 activation and viability. The expression of the antioxidant protein HO-1 was assessed by Western Blot. Results: No direct antioxidant effects of CA and GS have been reported on the HEK 293 TRex cell line. However, the ROS production was significantly decreased (30%) after 96h pre-incubation with 500μg/ml CA. The proMMP1 expression was shown to be modulated by Nox4 derived ROS in C-20/A4 chondrocytes. The results have shown a significant decrease in proMMP1 expression (40%) in CA treated chondrocytes but not after GS treatment. This effect was dependant on ginger root and copper sulfate. Furthermore, ADAMTS5 expression was markedly decreased by GS and CA but not by ginger root and copper sulfate. On the other hand, there was no effect on proMMP13 expression. Moreover, results reported a significant decrease in the IL-1β induced caspase 3 activation in presence of GS and CA. Our data suggest that molecular mechanisms could involve HO-1. Conclusions: In this study we provided experimental evidence in vitro that glucosamine sulfate decreases ADAMTS5 expression and apoptosis in the IL-1β stimulated C-20/A4 chondrocytes. In addition, ginger root and copper sulfate decrease the Nox4 regulated proMMP1 expression. These findings emphasize in vitro the potential beneficial effects of Cuivramine in osteoarthritis. References: Grange L, Nguyen MV, Lardy B, Derouazi M, Campion Y, Trocme C, Paclet MH, Gaudin P, Morel F (2006). NAD(P)H oxidase activity of Nox4 in chondrocytes is both inducible and involved in collagenase expression. Antioxid. Redox Signal 8: 1485-1496. Disclosure of Interest: None Declared